Gelam Honey Attenuates the Oxidative Stress-Induced Inflammatory Pathways in Pancreatic Hamster Cells - Safi, S.Z.; Batumalaie, K.; Qvist, R.; Yusof, K.M.; Ismail, Ikram Shah (Hindawi, 2016)
Purpose. Type 2 diabetes consists of progressive hyperglycemia and insulin resistance, which could result from glucose toxicity, inflammatory cytokines, and oxidative stress. In the present study we investigated the effect of Gelam honey and quercetin on the oxidative stress-induced inflammatory pathways and the proinflammatory cytokines. Methods. HIT-T15 cells were cultured and preincubated with the extract of Gelam honey (20, 40, 60, and 80 μg/mL), as well as quercetin (20, 40, 60, and 80 μM), prior to stimulation by 20 and 50 mM glucose. Results. HIT-T15 cells cultured under hyperglycemic condition showed a significant increase in the inflammatory pathways by phosphorylating JNK, IKK-β, and IRS-1 at Ser307 (). There was a significant decrease in the phosphorylation of Akt at Ser473 (). Pretreatment with Gelam honey and quercetin reduced the expression of phosphorylated JNK, IKK-β, and IRS-1, thereby significantly reducing the expression of proinflammatory cytokines like TNF-α, IL-6, and IL-1β (). At the same time there was a significant increase in the phosphorylated Akt showing the protective effects against inflammation and insulin resistance (). In conclusion, our data suggest the potential use of the extract from Gelam honey and quercetin in modulating the inflammation induced insulin signaling pathways.